Unveiling Hidden Hyperuniformity: Radial Turing Pattern Formation of Marangoni‐Driven SiO2 Nanoparticles on Liquid Metal Surface - Jinjian Guo; Jie Chen; Kang Zhao; Xuedong Bai; Wenlong Wang (Advanced Science)
Abstract Mastering the self‐organization of nanoparticle morphologies is pivotal in soft matter physics and film growth. Silicon dioxide (SiO2) nanoparticles are an archetypical model of nanomotor in soft matter. Here, the emphasis is on the self‐organizing behavior of SiO2 nanoparticles under extreme conditions. It is unveiled that manipulating the states of the metal substrate profoundly dictates the motion characteristics of SiO2 nanoparticles. This manipulation triggers the emergence of intricate morphologies and distinctive patterns. Employing a reaction‐diffusion model, the fundamental roles played by Brownian motion and Marangoni‐driven motion in shaping fractal structures and radial Turing patterns are demonstrated, respectively. Notably, these radial Turing patterns showcase hyperuniform order, challenging conventional notions of film morphology. These discoveries pave the way for crafting non‐equilibrium morphological materials, poised with the potential for self‐healing, adaptability, and innovative applications.